Duodenal bacterial overgrowth during treatment in outpatients with omeprazole. Issue 1 (January 1994) - Fried, M; Siegrist, H; Frei, R; Froehlich, F; Duroux, P; Thorens, J; Blum, A; Bille, J; Gonvers, J J; Gyr, K
Abstract : The extent of duodenal bacterial overgrowth during the pronounced inhibition of acid secretion that occurs with omeprazole treatment is unknown. The bacterial content of duodenal juice of patients treated with omeprazole was therefore examined in a controlled prospective study. Duodenal juice was obtained under sterile conditions during diagnostic upper endoscopy. Aspirates were plated quantitatively for anaerobic and aerobic organisms. Twenty five outpatients with peptic ulcer disease were investigated after a 5.7 (0.5) weeks (mean (SEM)) treatment course with 20 mg (nine patients) or 40 mg (16 patients). The control group consisted of 15 outpatients referred for diagnostic endoscopy without prior antisecretory treatment. No patient in the control group had duodenal bacterial overgrowth. In the omeprazole group bacterial overgrowth (> or = 10(5) cfu/ml) was found in 14 (56%) patients (p = 0.0003). The number of bacteria (log10) in duodenal juice in patients treated with omeprazole was distinctly higher (median 5.7; range < 2-8.7) when compared with the control group (median < 2; range < 2-5.0; p = 0.0004). As well as orally derived bacteria, faecal type bacteria were found in seven of 14 and anaerobic bacteria in three of 14 patients. Bacterial overgrowth was similar with the two doses of omeprazole. These results indicate that duodenal bacterial overgrowth of both oral and faecal type bacteria occurs often in ambulatory patients treated with omeprazole. Further studies are needed to determine the clinical significance of these findings, particularly in high risk groups during long term treatment with omeprazole.